Blended Learning Using Schoology as an Online Learning Platform: Potentials and Challenges - Muhtia, Anggri; Suparno, Suparno; Sumardi, Sumardi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The emphasis of educational instruction has shifted from teaching to learning where the role of teachers is not knowledge transmitters but the facilitators, knowledge navigators, and co-learners. Advanced technologies have a place in the shifting of teacher roles, for example the Internet technology which enables online learning to be held to enhance the teacher roles in facilitating learning. Online learning integrated into face-to-face learning which is called blended learning is believed to be more beneficial than online learning or face-to-face learning alone. However, despite the substantial benefits of blended learning frequently mentioned, teachers are still reluctant in implementing blended learning in their practices. This literature study reviews several papers studying the potentials and challenges of blended learning using Schoology as an online learning platform. The purpose of the study is to find out the potentials and the challenges of blended learning using Schoology. It is expected that the findings will raise teacher awareness about the importance of bringing technologies in their practices, encourage teachers to utilize online learning platforms such as Schoology in blended learning environment, and draw attention of education practitioners and any relevant parties to participate in addressing the challenges of blended learning to improve studentsâ€Ÿ learning experiences. Â